2021
DOI: 10.47895/amp.v55i6.3412
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Profile of Vehicular Accident Patients in the Largest Hospital in the Philippines Covering Ten Years

Abstract: Introduction. Globally, the number of people who die from road crashes continues to rise, reaching a high of 1.35 million in 2016. Due to this continued increase in fatalities and injuries within the road transport system, especially in low- and middle-income countries, 2011 to 2020 was declared by the United Nations General Assembly in 2010 as the Decade of Action for Road Safety. Objectives. This study looked into the epidemiology of road crashes and injuries in Metro Manila over ten years, from 2008-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Makkah and Madinah, the two Islamic holiest cities, have also recorded an unprecedented incidence of ambulance crashes [ 1 , 2 ]. The high population and urbanization of these cities and the higher frequency of traffic could account for the number of accidents, as they are consistent with studies from other countries [ 17 , 18 ]. A recent study from Saudi Arabia analyzed the national data of EMS response time for RTAs and reported the capital city of Riyadh marked the highest proportion of the RTAs followed by Makkah region [ 16 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…Makkah and Madinah, the two Islamic holiest cities, have also recorded an unprecedented incidence of ambulance crashes [ 1 , 2 ]. The high population and urbanization of these cities and the higher frequency of traffic could account for the number of accidents, as they are consistent with studies from other countries [ 17 , 18 ]. A recent study from Saudi Arabia analyzed the national data of EMS response time for RTAs and reported the capital city of Riyadh marked the highest proportion of the RTAs followed by Makkah region [ 16 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…The two holiest towns in Islam, Makkah and Madinah, have likewise seen an unusual number of ambulance crashes [34]. Since the number of accidents is consistent with research from other nations, the high population density, urbanization, and increased traffic frequency of major cities may cause the accidents [35]. According to recent Saudi Arabian research that examined national statistics on EMS response times for RTAs, Riyadh, the country's capital, had the most percentage of RTAs, followed by the Makkah area [7].…”
Section: Discussionmentioning
confidence: 61%
“…Bucsuhazy and colleagues conducted another study that emphasized the complexity of accident causation and the significance of examining factors such as human behavior and environmental circumstances that lead to accidents [34]. In their study of motorbike accidents in Ethiopia, Oltaye and co-authors found a significant frequency of RTA patients, especially in males between the ages of 20 and 29 [35]. They also discovered significant correlations between age, sex, speed, and the type of road.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The provision of the hospital with these expensive implants have made it more accessible to more patients especially those belonging in the lowest income status who are mostly the subset affected by facial fractures from vehicular crash or trauma. 19 , 20…”
Section: Discussionmentioning
confidence: 99%